Does Dysmenorrhea Affect Clinical Features and Long-Term Surgical Outcomes of Patients With Ovarian Endometriosis? A 12-Year Retrospective Observational Cohort Study - Wu, Yushi; Li, Xiaoyan; Dai, Yi; Shi, Jinghua; Gu, Zhiyue; Zhang, Jing; Zhang, Chenyu; Yan, Hailan; Leng, Jinhua (Frontiers in Medicine, 2022)
Abstract Background: To examine and compare differences in clinical characteristics and long-term postoperative outcomes in ovarian endometriosis (OMA) patients with and without dysmenorrhea, including data from at least 8 years of postoperative follow-up examinations. Methods: Retrospective analysis of 334 OMA patients, including their minimum of 8 years of post-laparoscopic follow-up reports. All laparoscopic cystectomy procedures were performed by the same surgeon at Peking Union Medical College Hospital between January 2009 and April 2013. Patients were divided into the dysmenorrhea and non-dysmenorrhea groups to perform the analysis of their preoperative characteristics, relevant surgical findings, and postoperative outcomes at the follow-up. Results: Out of 334 OMA patients, 257 (76.9%) patients were allocated to the dysmenorrhea group, while the rest 77 (23.1%) patients were included in the non-dysmenorrhea group. Compared with the dysmenorrhea group, the non-dysmenorrhea group exhibited a reduced proportion of CPP (P=0.003), dyspareunia (P<0.001), tenesmus(P<0.001), concurrency of DIE (P<0.001), and adenomyoma (P=0.032). Preoperative infertility was significantly higher in the dysmenorrhea group (P=0.001). The mean operating time in the dysmenorrhea vs. the non-dysmenorrhea group was 68.0 vs. 56.0 min (P<0.001). According to the revised AFS (rAFS) scoring system, the mean scores of the two groups were 52.1 vs. 44.6 (P=0.033). After the follow-up, the dysmenorrhea group showed a higher rate of disease relapse (P<0.001). A minimum postoperative follow-up period of 8 years was required to identify the cases of successful live birth and failed pregnancy [97/257 (37.7%) and 160/257 (62.3%), respectively] in the dysmenorrhea group vs. 36/77(46.8%) and 41/77 (53.2%) cases, respectively, in the non-dysmenorrhea group (P=0.157). Though the dysmenorrhea group had a higher rate of postoperative infertility, however, differences were not significant between the two groups. Conclusions: Compared with the dysmenorrhea group, EM patients without dysmenorrhea exhibited lower proportions of CPP, dyspareunia, tenesmus, lower concurrency of DIE and adenomyoma, shorter mean operating time, lower mean rAFS scores, and lower infertility rates. During the long-term follow-up, a lower recurrence rate was observed in the non-dysmenorrhea group. Regarding fertility outcomes, dysmenorrhea patients had a lower likelihood of successful pregnancy after surgery. Postoperative management needs to be evaluated separately according to dysmenorrhea pathology.